The importance of visual control in the process of maintaining the balance of the body - Pankanin, Ewelina Stefania (Journal of Education, Health and Sport, 2018)
Maintaining body balance is a complex process influenced by many components, ie the organ of balance, proprioceptors and the organ of sight. Keeping your balance allows you to safely perform your daily life activities. In the case of impairment of one of the components of the equilibrium system, the postural control process is disturbed. In this situation, other sensory systems are involved to partially compensate for the deficiencies. In the case of turning off the visual inspection, the body balance is strongly disturbed as evidenced by the results of scientific research.